Postcontrast Fluid-Attenuated Inversion Recovery (FLAIR) Sequence MR Imaging in Detecting Intracranial Pathology - Ajit Mahale; Shaloo Choudhary; Sonali Ullal; Merwyn Fernandes; Sonali Prabhu (Radiology Research and Practice)
Background. Imaging sequences for detection of meningeal and parenchymal lesions are critical in intracranial pathology. Our study analysed FLAIR MRI sequence for evaluating postcontrast enhancement. Objectives. FLAIR imaging sequences have been used in evaluation of enhancement in the brain. We conducted a study of FLAIR imaging sequences to better delineate postcontrast enhancement. Materials and Methods. In this prospective hospital-based observational study, postcontrast T1 MTC and delayed postcontrast T2 FLAIR and T1 FLAIR images of 66 patients with intracranial pathology were assessed by experienced radiologists from November 2017 to November 2019. Results. 28 cases of meningeal enhancement were identified in delayed postcontrast T2 FLAIR images. Low-grade gliomas included in the study showed postcontrast enhancement on postcontrast T1 MTC images. Multiple sclerosis lesions were better seen on postcontrast T1 FLAIR. In extraaxial lesions of 11 cases of meningioma, brighter enhancement was seen on delayed postcontrast T2 FLAIR images. Conclusion. We found that delayed postcontrast T2 FLAIR was better in detection of meningeal enhancement in infectious meningitis and in meningitis carcinomatosis than T1 MTC images. In delayed postcontrast T2 FLAIR images, intra-axial parenchyma lesions appeared more conspicuous or similar to T1 MTC images. Delayed postcontrast T1 FLAIR images provided better anatomic delineation of intra-axial lesions.